Audit tenure and audit qualifications in a low litigation risk setting: an analysis of the spanish market - García Blandón, Josep; Argilés Bosch, Josep Maria (Estudios de Economía, 2013)
The main role of the external auditor in the classical corporate governance scheme is to verify the accounting information provided by the firms’ managers. Lengthy audit engagements are viewed as a main threat to preserve auditor independence, and therefore regulators have established mandatory rotation rules in many countries worldwide. Researchers, however, have addressed the analysis of audit independence mainly by evaluating the role of the auditor not as an accounting verifier but as a substitute of bankruptcy prediction models. Our results show that the likelihood of audit qualifications decreases with audit tenure. This result is robust to the inclusion in the model of a proxy of accounting quality. Therefore, the potential explanation for this finding based on higher accounting quality associated to lengthy audit engagements is rejected. This threat to the independence of the external auditor has not been considered in the mandatory rotation rules established in most countries that only requires the rotation of the audit partner.